Etiology and genetic evolution of canine coronavirus circulating in five provinces of China, during 2018–2019. (August 2020) - He, Hai-Jian; Zhang, Wenyan; Liang, Jiawei; Lu, Meng; Wang, Ruyi; Li, Gairu; He, Jia-Wei; Chen, Jun; Chen, Jun; Xing, Gang; Chen, Ye
Abstract: As the outbreaks of COVID-19 in worldwide, coronavirus has once again caught the attention of people. Canine coronavirus is widespread among dog population, and sometimes causes even fatal cases. Here, to characterize the prevalence and evolution of current circulating canine coronavirus (CCoV) strains in China, we collected 213 fecal samples from diarrheic pet dogs between 2018 and 2019. Of the 213 samples, we found 51 (23.94%) were positive for CCoV. Co-infection with canine parvovirus (CPV), canine astrovirus (CaAstV), canine kobuvirus (CaKV), Torque teno canis virus (TTCaV) were ubiquitous existed. Mixed infection of different CCoV subtypes exists extensively. Considering the limited sequences data in recent years, we sequenced 7 nearly complete genomes and 10 complete spike gene. Phylogenetic analysis of spike gene revealed a new subtype CCoV-II Variant and CCoV-IIa was the most prevalent subtype currently circulating. Moreover, we identified strain B906_ZJ_2019 shared 93.24% nucleotide identifies with previous strain A76, and both of them clustered with CCoV-II Variant, which were not well clustered with the known subtypes. Recombination analysis of B906_ZJ_2019 indicated that strain B906_ZJ_2019 may a recombinant variant between CCoV–I and CCoV-II, which is consistent with strain A76. Furthermore, amino acid variations widely existed among current CCoV-IIa strains circulating in China and the classic CCoV-IIa strains, in spite of the unknown functions. In a word, we report a useful information as to the etiology and evolution of canine coronavirus in China based on the available sequences, which is urgent for the devise of future effective disease prevention and control strategies. Highlights: Phylogenetic analysis revealed a new subtype CCoV-II Variant and currently the most prevalent subtype CCoV-IIa. Strain B906_ZJ_2019 shared 93.24% nucleotide identify with strain A76, and both of them clustered with CCoV-II Variant. Amino acid variations widely existed among current CCoV-IIa strains circulating in China and the classic CCoV-IIa strains.